Pembuatan Aplikasi Temu Kembali Arsip Berbasis Microsoft Excel Visual Basic for Applications di Dinas Perpustakaan Umum dan Arsip Daerah Kota Malang - Zakiah Nur Fadilah; Joni Dwi Pribadi (IAI Nasional Laa Roiba Bogor, 2026)
One regional apparatus that handles government matters in the area of libraries and archives is the Public Library and Regional Archives Service of Malang City. The main problem found was that the manual system in place made it take a long time to obtain archives. The aim of this research is to develop an application that enhances the management of incoming and outgoing letters at the public library and regular archives office (DISPUSSIPDA) in Malang, speeds up archive search procedures, and reduces input errors. Planning, action, observation, and reflection are the four cycles of the action research approach used in this study. Questionnaires, paperwork, interviews, and observations were used to gather the data. The object was the Excel VBA-based archive management tool, and the research subjects were the archivists of DISPUSSIPDA. The application was evaluated using archive retrieval time metrics and usability testing based on Nielsen’s five usability attributes. The results showed that the application reduced archive input time from 8 to 10 minutes to approximately 5 to 7 minutes, significantly improving retrieval efficiency. Usability testing indicated a “Very High” rating across all evaluated aspects. Features such as input forms, search tools, and report generation were deemed effective and aligned with user needs. In conclusion, the Excel VBA-based application provides a practical and efficient solution for active archive management. Future research may explore expanding the application to include inactive records and integrating it more broadly with the system.